Early Detection and Suppression of Thermal Runaway in Large-Format Lithium-Ion Batteries: Insights from Experimental Analysis - Sungsik Choi; Keunhyung Lee; Jaehoon Kim; Seun Oh; Jaehyun Joo; Eunsoo Bae; Hyeonu Lee; Misung Kim (Energies)
Lithium-ion batteries have been increasingly demonstrated in reuse applications for environmental and economic reasons, and stationary energy storage systems (ESS) and mobile ESS are emerging as reuse applications for electric vehicle batteries. Most mobile ESS deployments are at large scales, necessitating experimental data on thermal runaway (TR) to ensure comprehensive safety. In this study, TR induction and suppression experiments were conducted using fully charged NCM-based batteries at the cell (750 Wh), module (7.5 kWh), and pack (74 kWh) levels. The stepwise TR experiments measured changes in temperature, voltage, heat release rate, volatile organic compound concentrations, and vent gas composition. The suppression experiments assessed the effective water injection rate, timing, and volume required to mitigate TR propagation. The results demonstrate that in the case of TR caused by thermal abuse, early detection of battery abnormalities is possible through monitoring pre-TR indicators, such as temperature and vent gas concentration. It was also confirmed that CO2 injections can effectively cool the battery without causing damage. Furthermore, it is proposed that rapid water injection, directly contacting the battery immediately after the onset of TR, can successfully prevent TR propagation.